Study of Proton Leakage at Interface of Anion-Exchange Membrane in Solutions of Acids, Salts, and Solvents Using Current/Voltage Characteristics. Issue 4 (2nd April 2016) - Lachachi, Zoubida; Kameche, Mostefa; Bendjeda, Samih; Meddah, Kheira; Hamani, Houari; Boumediene, Haddou; Innocent, Christophe
Abstract : Water dissociation and proton leakage using the anionic exchange membrane (AMH) are studied by means of current/voltage characteristics and confirmed by simulation of transport number using Hittorf's method. The acids used are HCl, HNO3, and H2 SO4 and the salts are NaCl, ZnCl2, and NaNO3 . Concentration polarization of such membrane is accompanied by a change in the electrolyte concentration/solution interface due hydrolysis reactions. The results show that when the concentration of the electrolyte increases, the limiting current density increases linearly and the transmembrane resistance decreases systematically. The thickness of the diffusion layer is always higher in presence of acid than salt, making in evidence the proton leakage through the membrane. Besides, when the membrane is selectively permeable to chloride anion in the case of ZnCl2, the thickness of the double layer is rather bigger and far exceeds that of the membrane. The voltamperometry method seems reliable and offers some advantages over that of Hittorf because it shows the effects of some parameters on the value of limiting current: concentration, counter-ion types (Cl −, NO3 − SO4 2− ), and the gradient of concentration in the anode and cathode compartments. It can, therefore, allow to optimize the value of the current which should be used in electrodialysis in any form and without a great consumption of energy. Moreover, the simulation carried out for transport number of proton, shows its sensitivity toward the variation in concentration in the receiving compartment. In effect, a small decrease in concentration implies an enormous decrease in its value.